Extended-Release Niacin/Laropiprant Improves Overall Efficacy of Postprandial Reverse Cholesterol Transport. Issue 2 (February 2016) - El Khoury, Petra; Waldmann, Elisa; Huby, Thierry; Gall, Julie; Couvert, Philippe; Lacorte, Jean-Marc; Chapman, John; Frisdal, Eric; Lesnik, Philippe; Parhofer, Klaus G.; Le Goff, Wilfried; Guerin, Maryse
Abstract : Objectives—: Postprandial atherogenic lipoproteins, characterizing high-risk patients, correlate positively with cardiovascular events. Although the effect of niacin on fasting lipids is well established, its impact on atheroprotective reverse cholesterol transport (RCT) pathway and on functional features of circulating lipoproteins during the postprandial state remains indeterminate. Approach and Results—: We evaluated RCT pathway during postprandial phase in dyslipidemic patients displaying a low high-density lipoprotein (HDL) cholesterol phenotype. Ten subjects on stable statin therapy received 1 g/20 mg extended-release niacin/laropiprant (ERN/LRPT) for 4 weeks followed by 2 g/40 mg ERN/LRPT for additional 8 weeks. At each experimental period, postprandial hypertriglyceridemia and major steps of RCT, including cholesterol efflux from human macrophages, cholesteryl ester transfer protein–mediated cholesteryl ester transfer, and hepatic HDL-cholesteryl ester selective uptake were evaluated. Equally, the capacity of postprandial HDL particles isolated from patients before and after ERN/LRPT treatment to mediate RCT to feces was evaluated in vivo in human apolipoprotein B/cholesteryl ester transfer protein double transgenic mouse model. Compared with baseline, ERN/LRPT significantly reduced postprandial hypertriglyceridemia (incremental area under the curve-triglyceride: −53%; P =0.02). Postprandial increase in endogenous plasma cholesteryl ester transfer protein activity was completely abolished after ERN/LRPT treatment. Despite a slight reduction in plasma cholesterol efflux capacity from human THP-1 macrophages, evaluation of global RCT efficacy by combining both ex vivo and in vivo approaches indicate that postprandial HDL particles formed under ERN/LRPT therapy displayed a greater capacity for HDL-mediated RCT to feces. Conclusions—: ERN/LRPT treatment efficiently attenuates atherogenic postprandial lipemia and stimulates HDL-mediated cholesterol return to the liver and elimination into feces during postprandial phase, thus maintaining an efficient removal of cholesterol from the body. Abstract : Supplemental Digital Content is available in the text.